Integration Analysis of Community Satisfaction and Customer Satisfaction Index in Padang Public Service Mall - Amalda, Aviva; Magriasti, Lince (Universitas Airlangga, 2023)
MPP which stands for Public Service Mall is a building in which to practice services in the field of administration or licensing. The purpose of its establishment is to provide convenience, speed, security and comfort as well as affordable services for the community in receiving direct services in the same place. In this study, we will discuss the community satisfaction index using the customer satisfaction index (NCSI) at the Public Service Mall for the community in Padang City. Qualitative methods become the methods used which are research methods that produce descriptive data in the form of writing, speech, or object behavior. The data obtained is sourced from the official website of the Padang City Public Service Mall and from direct observations at the Padang City Public Service Mall. And it was obtained that the value of the Community Satisfaction Index for the Padang City Public Service Mall reached 87.30% with a perfect score above 95%. If referring to the ratio of CSI scores, the Community Satisfaction Index in MPP Padang City received a Good predicate with a value of 87.30%. This certainly brings a breath of fresh air which is expected to continue to evolve at higher numbers and better service quality as well. So it can be concluded that the community satisfaction index in the public service mall in Padang City is already at a good level according to the Customer Satisfaction Index standard. Keywords: Public Service; Community Satisfaction Index; Customer Satisfaction Index